The women who threw corn: witchcraft and Inquisition in sixteenth-century Mexico - Nesvig, Martin Austin (Cambridge University Press, 2025)
"This book tells the stories of women from Spain, North Africa, Senegambia, and Canaries accused of witchcraft in sixteenth-century Mexico for adapting native magic and healing practices. It will interest students and scholars of ethnohistory, Latin American studies, gender history, anthropology, and religious studies"--